Block copolymer grafted graphene oxide as well as preparation method and application thereof
The preparation method of grafting graphene oxide through block copolymer solves the problem of unsatisfactory modification of graphene oxide in the existing technology, achieves the improvement of mechanical properties and hydration control of cement-based materials, and has good application prospects.
Patent Information
- Application Number
- CN202411486133.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, physical modification and chemical modification of graphene oxide are not ideal to improve the performance of cement-based materials, especially the random molecular chain structure of graft copolymers, which affects the dispersion in the cement slurry.
The preparation method of the embedded segment cluster demented graphene is used to synthesize the polyether-polyetrylate embedded cluster through the RAFT polymerization branches. Essence
Achieve high decentralization of graphene in cement, improve the mechanical properties and regulation of cement base materials and regulation of hydration, and significantly improve the pressure resistance, folding strength and flow.
Smart Images

Figure CN119349918A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based material preparation, and in particular to a block copolymer grafted with graphene oxide, and a preparation method and application thereof. Background Art
[0002] In recent years, the consumption of cement-based materials has reached 3.6 billion tons per year, making it the world's largest and most widely used synthetic material. Traditional cement materials are porous and brittle materials with poor crack resistance and low tensile strength. Cement-based composite materials use silicate cement as the base material and add fiber materials or nanomaterials as reinforcement materials. Among them, fiber materials can only delay the development of macro and micro cracks, while nanomaterials can inhibit the generation of cracks at the nanoscale. Graphene oxide (GO for short) is a two-dimensional nanomaterial with a large specific surface area and excellent mechanical properties. Its surface also contains a large number of oxygen-containing groups (hydroxyl, carboxyl and epoxy groups, etc.), which provide good reaction sites for subsequent GO chemical modification, and show good application prospects in improving the strength, toughness and durability of cement-based materials.
[0003] At present, researchers have carried out physical and chemical modification on graphene oxide to improve the performance of cement-based materials, but most physical modification does not significantly enhance the mechanical properties of cement-based materials, and chemical modification is basically conventional free radical polymerization. The molecular chain structure of the grafted copolymer is random, which affects the dispersion of grafted graphene oxide in cement paste. Therefore, a new method for modifying graphene oxide is urgently needed. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a block copolymer grafted graphene oxide and a preparation method and application thereof, so as to solve the problem in the prior art that physical and chemical modifications of graphene oxide are not ideal for improving the performance of cement-based materials.
[0005] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a block copolymer grafted with graphene oxide is provided, comprising the following steps:
[0006] (1) Esterification reaction: Graphene oxide is dispersed in a solvent, and a RAFT agent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide are added in sequence, reacting for 23-25 hours, washing and drying to obtain RAFT agent-modified graphene oxide;
[0007] (2) Graft copolymerization: dispersing the RAFT agent modified graphene oxide obtained in step (1) in a solvent, adding a polyether copolymer and an initiator in sequence, reacting at 65-75° C. under a nitrogen atmosphere for 7-9 hours, washing and drying to obtain a copolymer grafted graphene oxide;
[0008] (3) Block copolymerization: The copolymer grafted graphene oxide obtained in step (2) is dispersed in a solvent, polypropene sulfonic acid and an initiator are added in sequence, reacted at 65-75° C. under a nitrogen atmosphere for 7-9 hours, washed and dried to obtain a block copolymer grafted graphene oxide.
[0009] On the basis of the above technical solution, the present invention can also be improved as follows:
[0010] Further, in step (1), graphene oxide is prepared by the following method:
[0011] S1: Mix graphite powder and sodium nitrate, add concentrated sulfuric acid solution and potassium permanganate in turn under ice bath condition, react at 40-50°C for 2.5-3.5h, add deionized water to obtain reaction solution 1;
[0012] S2: react the reaction solution 1 obtained in step S1 at 90-100° C. for 1.8-2.2 h, add deionized water and hydrogen peroxide solution in sequence, cool to room temperature, add hydrochloric acid solution, let stand, centrifuge, wash with water and dry to obtain graphene oxide.
[0013] The beneficial effects of adopting the above further technical solutions are: strong customizability. The preparation parameters, such as oxidation degree, sheet size, etc., can be precisely adjusted according to the needs of the next experiment. Low cost. Self-preparation can meet the large demand for graphene oxide in the laboratory, and can also avoid the high cost of market purchase. Quality control is guaranteed. Strict monitoring and quality testing during the preparation process ensure the purity and quality of graphene oxide, and reduce the uncertainty of experimental results caused by quality fluctuations.
[0014] Further, in step S1, the mass volume ratio of graphite powder, sodium nitrate, potassium permanganate, concentrated sulfuric acid and deionized water is 1.8-2.2 g: 0.8-1.2 g: 4-8 g: 45-55 mL: 55-65 mL.
[0015] Furthermore, in step S1, the mass volume ratio of graphite powder, sodium nitrate, potassium permanganate, concentrated sulfuric acid and deionized water is 2g:1g:6g:50mL:60mL.
[0016] Furthermore, in step S1, the concentration of the concentrated sulfuric acid solution is 98 wt%.
[0017] Furthermore, in step S1, the reaction is carried out at 45° C. for 3 h.
[0018] Further, in step S2, the reaction is carried out at 95° C. for 2 h.
[0019] Furthermore, in step S2, the volume mass ratio of deionized water, hydrogen peroxide solution, hydrochloric acid solution and graphite powder is 95-105 mL: 5-7 mL: 4-6 mL: 1.8-2.2 g.
[0020] Furthermore, in step S2, the volume mass ratio of deionized water, hydrogen peroxide solution, hydrochloric acid solution and graphite powder is 100 mL: 6 mL: 5 mL: 2 g.
[0021] Furthermore, in step S2, the concentration of the hydrogen peroxide solution is 25-35 wt%.
[0022] Furthermore, in step S2, the concentration of the hydrogen peroxide solution is 30 wt%.
[0023] Further, in step S2, the concentration of the hydrochloric acid solution is 8-12 wt%.
[0024] Furthermore, in step S2, the concentration of the hydrochloric acid solution is 10 wt%.
[0025] Further, in step S2, the mixture is allowed to stand for 8-12 hours.
[0026] Further, in step S2, washing is performed with water until the Ph value of the supernatant is 7.
[0027] Further, in step S2, freeze drying is performed for 45-50 hours.
[0028] Further, in step S2, freeze drying is performed for 48 hours.
[0029] Furthermore, in step (1), the volume mass ratio of the solvent, graphene oxide, RAFT agent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide is 90-110 mL: 0.5-0.7 g: 2.5-3 g: 0.5-0.6 g: 1.5-1.6 g.
[0030] Furthermore, in step (1), the volume mass ratio of the solvent, graphene oxide, RAFT agent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide is 100 mL: 0.6 g: 2.8 g: 0.56 g: 1.568 g.
[0031] Furthermore, in steps (1)-(3), the solvent is N,N-dimethylformamide.
[0032] Furthermore, in steps (1) to (3), the reaction is first carried out at room temperature for 0.3-0.8 h, and then ultrasonicated for 0.3-0.8 h to complete the dispersion process.
[0033] Furthermore, in steps (1)-(3), the reaction is first carried out at room temperature for 0.5 h, and then ultrasonicated for 0.5 h to complete the dispersion process.
[0034] Furthermore, in step (1), the RAFT agent is 2-(dodecylthiocarbonylthio)-2-methylpropanoic acid or 4-cyano-4-(phenylthioformylthio)pentanoic acid.
[0035] Furthermore, in step (1), the reaction is carried out at room temperature.
[0036] Furthermore, in step (1), the reaction is carried out for 24 hours.
[0037] Furthermore, in steps (1)-(3), dichloromethane is used for washing until the supernatant is colorless.
[0038] Furthermore, in steps (1)-(3), vacuum drying is performed for 10-15 hours.
[0039] Furthermore, in steps (1)-(3), vacuum drying was performed for 12 h.
[0040] Furthermore, in step (2), the volume mass ratio of the solvent, the RAFT agent modified graphene oxide, the polyether copolymer and the initiator is 90-110 mL: 0.4-0.6 g: 1.2-1.3 g: 0.1-0.3 g.
[0041] Furthermore, in step (2), the volume mass ratio of the solvent, the RAFT agent modified graphene oxide, the polyether copolymer and the initiator is 100 mL: 0.5 g: 1.25 g: 0.2 g.
[0042] Furthermore, in step (2), the polyether copolymer is polyethylene glycol methyl ether acrylate, methoxy polyethylene glycol acrylate or allyl polyethylene glycol.
[0043] Furthermore, in step (2), the initiator is azobisisobutyronitrile.
[0044] Furthermore, in step (2), the reaction is carried out at 70° C. for 8 h.
[0045] Furthermore, in step (3), the volume mass ratio of the solvent, copolymer grafted graphene oxide, polypropanesulfonic acid and initiator is 140-160 mL: 0.4-0.6 g: 12-13 g: 0.1-0.3 g.
[0046] Furthermore, in step (3), the volume mass ratio of the solvent, copolymer-grafted graphene oxide, polypropanesulfonic acid and initiator is 150 mL: 0.5 g: 12.5 g: 0.2 g.
[0047] Furthermore, in step (3), the polypropane sulfonic acid is 2-acrylamido-2-methylpropane sulfonic acid, aminoethanesulfonic acid or acrylic acid.
[0048] Furthermore, in step (3), the initiator is azobisisobutyronitrile.
[0049] Furthermore, in step (3), the reaction is carried out at 70° C. for 8 h.
[0050] The present invention also provides the block copolymer grafted graphene oxide prepared by the method.
[0051] The present invention also provides application of the block copolymer grafted with graphene oxide in the preparation of cement-based composite materials.
[0052] Furthermore, the block copolymer grafted graphene oxide is dispersed in water to obtain a dispersion, and cement, sand and the dispersion are mixed to prepare cement mortar, that is, a cement-based composite material.
[0053] Furthermore, the mass fraction of the block copolymer grafted graphene oxide in cement is 0.01-0.1%.
[0054] Furthermore, the mass fraction of the block copolymer grafted graphene oxide in the cement is 0.05%.
[0055] Furthermore, the mass ratio of cement to water is 0.5.
[0056] Furthermore, the mass ratio of cement to sand is 450:1350.
[0057] Furthermore, the sand is Chinese ISO standard sand.
[0058] The present invention has the following beneficial effects:
[0059] 1. The present invention starts from the theory of molecular structure design, chemically modifies graphene oxide, adopts the first RAFT polymerization grafted block copolymer, and synthesizes polyether-polyacrylic acid block copolymer. The adsorption groups in its structure are more concentrated and exposed, and it has good dispersion and adsorption in cement paste to regulate the cement hydration process. It is an innovation to apply modified graphene oxide in cement.
[0060] 2. The block copolymer grafted with graphene oxide synthesized in the present invention has a strong adsorption capacity on the surface of inorganic particles, and provides a relatively large steric hindrance, interacts at the interface between graphene oxide sheets, optimizes the structure-activity relationship, and realizes high dispersion of graphene oxide sheets in the grafted block copolymer matrix. This product provides a unique graphene oxide modification idea and has good application prospects and market competitiveness.
[0061] 3. The synthesis method of the present invention is simple, the reaction raw materials are common, the whole reaction process is simple and controllable, the oxidation and polymerization reaction steps used have no special requirements on experimental equipment and experimental links, and it is easy to realize industrial production.
[0062] 4. The preparation process of this product has low energy consumption, is safe and environmentally friendly, and uses low-priced polypropene sulfonic acid, which reduces the cost of the product. In addition, the product can achieve good results at a low dosage in cement, thereby improving product competitiveness and development prospects.
[0063] 5. The product of the present invention has a good promoting effect in the cement hydration process, can improve the workability of cement-based materials, strengthen the mechanical properties of cement-based materials, and can obtain good economic benefits. Specifically, it can increase the compressive strength of cement by 5-10Mpa, the flexural strength by 1-4Mpa, the fluidity by 2-8mm, and the total heat release of cement hydration by 20J·g -1 , the adiabatic temperature rise is 6℃, and it has good development and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 It is a reaction flow chart of the present invention;
[0065] Figure 2 is the structural formula of the RAFT agent modified graphene oxide of the present invention;
[0066] Figure 3 is the structural formula of the copolymer grafted with graphene oxide of the present invention;
[0067] Figure 4 It is the structural formula of the block copolymer grafted with graphene oxide of the present invention. DETAILED DESCRIPTION
[0068] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0069] The structural formula of RAFT is
[0070] The structural formula of OEGMA is
[0071] The structural formula of AMPS is Embodiment 1:
[0072] A block copolymer grafted with graphene oxide, the preparation method of which comprises the following steps (reaction flow chart see Figure 1 ):
[0073] (1) Oxidation reaction:
[0074] S1: Add graphite powder to a 250mL three-necked flask, add sodium nitrate under stirring, slowly add concentrated sulfuric acid solution (concentration of 98wt%) and potassium permanganate in turn under ice bath conditions, react at 45°C for 3h, slowly add deionized water to obtain reaction solution 1; wherein the mass volume ratio of graphite powder, sodium nitrate, potassium permanganate, concentrated sulfuric acid and deionized water is 2g:1g:6g:50mL:60mL;
[0075] S2: react the reaction solution 1 obtained in step S1 at 95°C for 2h, slowly add deionized water and hydrogen peroxide solution (concentration of 30wt%) in sequence, cool to room temperature, add hydrochloric acid solution (concentration of 10wt%), let stand for 8-12h, centrifuge, wash with water until the supernatant has a Ph value of 7, freeze-dry for 48h, and obtain graphene oxide (GO); wherein the volume mass ratio of deionized water, hydrogen peroxide solution, hydrochloric acid solution and graphite powder is 100mL:6mL:5mL:2g;
[0076] (2) Esterification reaction: The graphene oxide prepared in step S2 and the solvent (N,N-dimethylformamide) were added to a 250 mL three-necked flask, reacted at room temperature for 0.5 h, and then ultrasonicated for 0.5 h to disperse the graphene oxide in the solvent; RAFT reagent (2-(dodecylthiocarbonylthio)-2-methylpropionic acid) and 4-dimethylaminopyridine were added in sequence, and tricyclohexylcarbodiimide was added after stirring, and reacted for 24 h. The mixture was washed with an eluent (dichloromethane) until the supernatant was colorless, and vacuum dried for 12 h to obtain RAFT reagent-modified graphene oxide (GO-RAFT, see Figure 2 ); wherein the volume mass ratio of the solvent, graphene oxide, RAFT agent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide is 100 mL: 0.6 g: 2.8 g: 0.56 g: 1.568 g;
[0077] (3) Graft copolymerization: The RAFT agent modified graphene oxide prepared in step (2) and the solvent (N,N-dimethylformamide) were added to a 250 mL three-necked flask, reacted at room temperature for 0.5 h, and then ultrasonicated for 0.5 h to disperse the RAFT agent modified graphene oxide in the solvent; then the polyether copolymer (OEGMA, polyethylene glycol methyl ether acrylate) and the initiator (azobisisobutyronitrile) were slowly added in sequence, and nitrogen was continuously introduced for 0.5 h. The nitrogen was kept introduced and reacted at 70° C. under a nitrogen atmosphere for 8 h. The mixture was washed with an eluent (dichloromethane) until the supernatant was colorless and dried in vacuum for 12 h to obtain a copolymer grafted graphene oxide (GO-g-POEGMA, see Figure 3 ); wherein the volume mass ratio of the solvent, the RAFT agent modified graphene oxide, the polyether copolymer and the initiator is 100 mL: 0.5 g: 1.25 g: 0.2 g;
[0078] (4) Block copolymerization: The copolymer grafted graphene oxide obtained in step (3) and solvent (N,N-dimethylformamide) were added to a 250 mL three-necked flask, reacted at room temperature for 0.5 h, and then ultrasonicated for 0.5 h to disperse the copolymer grafted graphene oxide in the solvent; polypropane sulfonic acid (AMPS, 2-acrylamido-2-methylpropane sulfonic acid) and initiator (azobisisobutyronitrile) were then slowly added in sequence, and nitrogen was continuously introduced for 0.5 h. The nitrogen was kept introduced and reacted at 70° C. for 8 h under nitrogen atmosphere. The block copolymer grafted graphene oxide (GO-g-POE-b-PAMPS, see Figure 4 ); wherein the volume mass ratio of the solvent, copolymer grafted graphene oxide, polypropanesulfonic acid and initiator is 150 mL: 0.5 g: 12.5 g: 0.2 g.
[0079] A cement-based composite material, the preparation method of which comprises the following steps:
[0080] 0.045g of the block copolymer grafted graphene oxide was added to 225g of water, and ultrasonicated for 0.5h until completely dispersed to obtain a dispersion, and 450g of cement, 1350g of Chinese ISO standard sand and 225g of the dispersion were mixed to obtain cement mortar, i.e., cement-based composite material. (The amount of the block copolymer grafted graphene oxide in cement was 0.01wt%, and the mass ratio of cement to water was 0.5)
[0081] The cement mortar was prepared into samples, placed in a standard curing room at 20°C and 95% relative humidity, and cured for 3 days to measure the implementation effect.
[0082] Embodiment 2-3:
[0083] A block copolymer grafted with graphene oxide, the preparation method of which comprises the following steps:
[0084] Same as Example 1.
[0085] A cement-based composite material, the preparation method of which comprises the following steps:
[0086] Same as Example 1.
[0087] Cement mortar was prepared into samples and placed in a standard curing room at 20°C and 95% relative humidity for 7 and 28 days, respectively, and the implementation effects were measured.
[0088] Embodiment 4-6:
[0089] A block copolymer grafted with graphene oxide, the preparation method of which comprises the following steps:
[0090] Same as Example 1.
[0091] A cement-based composite material, the preparation method of which comprises the following steps:
[0092] 0.135g of the block copolymer grafted graphene oxide was added to 225g of water, and the rest was the same as in Example 1 to prepare cement mortar, i.e., cement-based composite material. (The amount of the block copolymer grafted graphene oxide in cement was 0.03wt%, and the mass ratio of cement to water was 0.5).
[0093] Cement mortar was prepared into samples and placed in a standard curing room at 20°C and 95% relative humidity for 3, 7 and 28 days, and the implementation effects were measured.
[0094] Embodiment 7-9:
[0095] A block copolymer grafted with graphene oxide, the preparation method of which comprises the following steps:
[0096] Same as Example 1.
[0097] A cement-based composite material, the preparation method of which comprises the following steps:
[0098] 0.225g of the block copolymer grafted graphene oxide was added to 225g of water, and the rest was the same as in Example 1 to prepare cement mortar, i.e., cement-based composite material. (The amount of the block copolymer grafted graphene oxide in cement was 0.05wt%, and the mass ratio of cement to water was 0.5).
[0099] Cement mortar was prepared into samples and placed in a standard curing room at 20°C and 95% relative humidity for 3, 7 and 28 days, and the implementation effects were measured.
[0100] Embodiment 10-12:
[0101] A block copolymer grafted with graphene oxide, the preparation method of which comprises the following steps:
[0102] Same as Example 1.
[0103] A cement-based composite material, the preparation method of which comprises the following steps:
[0104] 0.45g of the block copolymer grafted graphene oxide was added to 225g of water, and the rest was the same as in Example 1 to prepare cement mortar, i.e., cement-based composite material. (The amount of the block copolymer grafted graphene oxide in cement was 0.1wt%, and the mass ratio of cement to water was 0.5).
[0105] Cement mortar was prepared into samples and placed in a standard curing room at 20°C and 95% relative humidity for 3, 7 and 28 days, and the implementation effects were measured.
[0106] Embodiment 13:
[0107] A block copolymer grafted with graphene oxide, the preparation method of which comprises the following steps:
[0108] (1) Oxidation reaction:
[0109] S1: Add graphite powder to a 250mL three-necked flask, add sodium nitrate under stirring, slowly add concentrated sulfuric acid solution (concentration of 98wt%) and potassium permanganate in turn under ice bath conditions, react at 40°C for 3.5h, slowly add deionized water to obtain reaction solution 1; wherein the mass volume ratio of graphite powder, sodium nitrate, potassium permanganate, concentrated sulfuric acid and deionized water is 1.8g:0.8g:4g:45mL:55mL;
[0110] S2: react the reaction solution 1 obtained in step S1 at 90°C for 2.2h, slowly add deionized water and hydrogen peroxide solution (concentration of 25wt%) in sequence, cool to room temperature, add hydrochloric acid solution (concentration of 8wt%), let stand for 8h, centrifuge, wash with water until the supernatant has a Ph value of 7, freeze-dry for 45h, and obtain graphene oxide; wherein the volume mass ratio of deionized water, hydrogen peroxide solution, hydrochloric acid solution and graphite powder is 95mL:5mL:4mL:1.8g;
[0111] (2) Esterification reaction: The graphene oxide obtained in step S2 and the solvent (N,N-dimethylformamide) were added to a 250 mL three-necked flask, reacted at room temperature for 0.3 h, and then ultrasonicated for 0.3 h to disperse the graphene oxide in the solvent; RAFT reagent (2-(dodecylthiocarbonylthio)-2-methylpropionic acid) and 4-dimethylaminopyridine were added in sequence, and tricyclohexylcarbodiimide was added after stirring, and reacted for 23 h. The mixture was washed with an eluent (dichloromethane) until the supernatant was colorless, and vacuum dried for 10 h to obtain RAFT reagent-modified graphene oxide; wherein the volume mass ratio of the solvent, graphene oxide, RAFT reagent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide was 90 mL: 0.5 g: 2.5 g: 0.5 g: 1.5 g;
[0112] (3) Graft copolymerization: The RAFT agent modified graphene oxide and solvent (N,N-dimethylformamide) prepared in step (2) are added to a 250 mL three-necked flask, reacted at room temperature for 0.3 h, and then ultrasonicated for 0.3 h to disperse the RAFT agent modified graphene oxide in the solvent; then, polyether copolymer (polyethylene glycol methyl ether acrylate) and initiator (azobisisobutyronitrile) are slowly added in sequence, and nitrogen is continuously introduced for 0.5 h. The nitrogen is kept introduced and reacted at 65° C. under a nitrogen atmosphere for 9 h. The mixture is washed with an eluent (dichloromethane) until the supernatant is colorless and vacuum dried for 10 h to obtain a copolymer grafted graphene oxide; wherein the volume mass ratio of the solvent, RAFT agent modified graphene oxide, polyether copolymer and initiator is 90 mL: 0.4 g: 1.2 g: 0.1 g.
[0113] (4) Block copolymerization: The copolymer grafted graphene oxide and solvent (N,N-dimethylformamide) prepared in step (3) are added to a 250 mL three-necked flask, reacted at room temperature for 0.3 h, and then ultrasonicated for 0.3 h to disperse the copolymer grafted graphene oxide in the solvent; polypropane sulfonic acid (2-acrylamido-2-methylpropane sulfonic acid) and initiator (azobisisobutyronitrile) are then slowly added in sequence, and nitrogen is continuously introduced for 0.5 h. The nitrogen is kept introduced and reacted at 65° C. under a nitrogen atmosphere for 9 h. The mixture is washed with an eluent (dichloromethane) until the supernatant is colorless and vacuum dried for 10 h to obtain a block copolymer grafted graphene oxide; wherein the volume mass ratio of the solvent, copolymer grafted graphene oxide, polypropane sulfonic acid and initiator is 140 mL: 0.4 g: 12 g: 0.1 g.
[0114] A cement-based composite material, the preparation method of which comprises the following steps:
[0115] 0.225g of the block copolymer grafted graphene oxide was added to 225g of water, and ultrasonicated for 0.5h until completely dispersed to obtain a dispersion, and 450g of cement, 1350g of Chinese ISO standard sand and 225g of the dispersion were mixed to obtain cement mortar, i.e., cement-based composite material. (The amount of the block copolymer grafted graphene oxide in cement was 0.05wt%, and the mass ratio of cement to water was 0.5)
[0116] Embodiment 14:
[0117] A block copolymer grafted with graphene oxide, the preparation method of which comprises the following steps:
[0118] (1) Oxidation reaction:
[0119] S1: Add graphite powder to a 250mL three-necked flask, add sodium nitrate while stirring, slowly add concentrated sulfuric acid solution (concentration of 98wt%) and potassium permanganate in turn under ice bath conditions, react at 50°C for 2.5h, slowly add deionized water to obtain reaction solution 1; wherein the mass volume ratio of graphite powder, sodium nitrate, potassium permanganate, concentrated sulfuric acid and deionized water is 2.2g:1.2g:8g:55mL:65mL;
[0120] S2: react the reaction solution 1 obtained in step S1 at 100°C for 1.8h, slowly add deionized water and hydrogen peroxide solution (concentration of 35wt%) in sequence, cool to room temperature, add hydrochloric acid solution (concentration of 12wt%), let stand for 12h, centrifuge, wash with water until the supernatant has a Ph value of 7, freeze-dry for 50h, and obtain graphene oxide; wherein the volume mass ratio of deionized water, hydrogen peroxide solution, hydrochloric acid solution and graphite powder is 105mL:7mL:6mL:2.2g;
[0121] (2) Esterification reaction: The graphene oxide obtained in step S2 and the solvent (N,N-dimethylformamide) were added to a 250 mL three-necked flask, reacted at room temperature for 0.8 h, and then ultrasonicated for 0.8 h to disperse the graphene oxide in the solvent; RAFT reagent (2-(dodecylthiocarbonylthio)-2-methylpropionic acid) and 4-dimethylaminopyridine were added in sequence, and tricyclohexylcarbodiimide was added after stirring, and reacted for 25 h. The mixture was washed with an eluent (dichloromethane) until the supernatant was colorless, and vacuum dried for 15 h to obtain RAFT reagent-modified graphene oxide; wherein the volume mass ratio of the solvent, graphene oxide, RAFT reagent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide was 110 mL: 0.7 g: 3 g: 0.6 g: 1.6 g;
[0122] (3) Graft copolymerization: The RAFT agent modified graphene oxide and solvent (N,N-dimethylformamide) prepared in step (2) are added to a 250 mL three-necked flask, reacted at room temperature for 0.8 h, and then ultrasonicated for 0.8 h to disperse the RAFT agent modified graphene oxide in the solvent; then, polyether copolymer (polyethylene glycol methyl ether acrylate) and initiator (azobisisobutyronitrile) are slowly added in sequence, and nitrogen is continuously introduced for 0.5 h. The nitrogen is kept introduced and reacted at 75° C. under a nitrogen atmosphere for 7 h. The mixture is washed with an eluent (dichloromethane) until the supernatant is colorless, and vacuum dried for 15 h to obtain a copolymer grafted graphene oxide; wherein the volume mass ratio of the solvent, RAFT agent modified graphene oxide, polyether copolymer and initiator is 110 mL: 0.6 g: 1.3 g: 0.3 g.
[0123] (4) Block copolymerization: The copolymer grafted graphene oxide and solvent (N,N-dimethylformamide) prepared in step (3) were added to a 250 mL three-necked flask, reacted at room temperature for 0.8 h, and then ultrasonicated for 0.8 h to disperse the copolymer grafted graphene oxide in the solvent; polypropane sulfonic acid (2-acrylamido-2-methylpropane sulfonic acid) and initiator (azobisisobutyronitrile) were then slowly added in sequence, and nitrogen was continuously introduced for 0.5 h. The nitrogen was kept introduced and reacted at 75° C. under a nitrogen atmosphere for 7 h. The mixture was washed with an eluent (dichloromethane) until the supernatant was colorless and vacuum dried for 15 h to obtain a block copolymer grafted graphene oxide; wherein the volume mass ratio of the solvent, copolymer grafted graphene oxide, polypropane sulfonic acid and initiator was 160 mL: 0.6 g: 13 g: 0.3 g.
[0124] A cement-based composite material, the preparation method of which comprises the following steps:
[0125] 0.225g of the block copolymer grafted graphene oxide was added to 225g of water, and ultrasonicated for 0.5h until completely dispersed to obtain a dispersion, and 450g of cement, 1350g of Chinese ISO standard sand and 225g of the dispersion were mixed to obtain cement mortar, i.e., cement-based composite material. (The amount of the block copolymer grafted graphene oxide in cement was 0.05wt%, and the mass ratio of cement to water was 0.5)
[0126] Test example
[0127] 1. Compression and flexural strength of cement
[0128] In order to investigate the mechanical properties of the block copolymer grafted with graphene oxide synthesized in the present invention on the modified cement-based composite material, the compressive strength and flexural strength of the cement mortar samples of each embodiment at different dosages were experimentally determined. The hardened cement mortar samples were tested according to GB / T 17671-1999 <Test method for strength of cement mortar (ISO method)>. The experimental results are shown in Table 1.
[0129] Table 1 Mechanical properties of cement mortar
[0130]
[0131] As can be seen from Table 1, by using the block copolymer grafted with graphene oxide of the present invention to modify cement-based materials, the compressive and flexural strengths of each embodiment group are higher than those of the blank group. When the block copolymer grafted with graphene oxide is added in an amount of 0.05wt% in cement, the reinforcement effect is the greatest, showing excellent mechanical properties of cement-based composite materials.
[0132] 2. Cement fluidity
[0133] In order to investigate the effect of the block copolymer grafted with graphene oxide synthesized in the present invention on the fluidity of cement, i.e., composite materials, the fluidity of cement paste of each embodiment at different dosages was experimentally determined. The test was carried out according to GB / T8077-2023 "Test method for homogeneity of concrete admixtures" and the water-cement ratio w / c was 0.35. The experimental results are shown in Table 2.
[0134] Table 2 Results of cement paste flow properties
[0135]
[0136] As can be seen from Table 2, the block copolymer grafted with graphene oxide synthesized in the present invention is modified on cement base, and the cement paste fluidity at different dosages shows excellent dispersibility compared with the blank group.
[0137] 3. Heat of Cement Hydration
[0138] In order to investigate the effect of the block copolymer grafted with graphene oxide synthesized in the present invention on the hydration heat performance of cement-based composite materials, the cement hydration heat and the adiabatic temperature rise of cement mortar in each embodiment at different dosages were experimentally determined, and the early hydration exothermic behavior of cement was analyzed using the TAM Air isothermal calorimeter of TAM Company of the United States. The test temperature was 23°C and the test time was 72h. The experimental results are shown in Table 3
[0139] Table 3 Parameters related to hydration heat test
[0140]
[0141]
[0142] As can be seen from Table 3, the block copolymer grafted with graphene oxide synthesized in the present invention is modified on cement-based materials. At a dosage of 0.05wt%, the total heat release of cement hydration and the adiabatic temperature rise of cement mortar are most significantly improved, showing an excellent effect in promoting cement hydration.
[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a block copolymer grafted with graphene oxide, characterized in that: The following steps are involved: (1) Esterification reaction: Graphene oxide is dispersed in a solvent, and a RAFT agent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide are added in sequence, reacting for 23-25 hours, washing and drying to obtain RAFT agent-modified graphene oxide; (2) Graft copolymerization: dispersing the RAFT agent modified graphene oxide obtained in step (1) in a solvent, adding a polyether copolymer and an initiator in sequence, reacting at 65-75° C. under a nitrogen atmosphere for 7-9 hours, washing and drying to obtain a copolymer grafted graphene oxide; (3) Block copolymerization: The copolymer grafted graphene oxide obtained in step (2) is dispersed in a solvent, polypropene sulfonic acid and an initiator are added in sequence, reacted at 65-75° C. under a nitrogen atmosphere for 7-9 hours, washed and dried to obtain a block copolymer grafted graphene oxide.
2. The method for preparing block copolymer grafted graphene oxide according to claim 1, characterized in that: In step (1), graphene oxide is prepared by the following method: S1: Mix graphite powder and sodium nitrate, add concentrated sulfuric acid solution and potassium permanganate in turn under ice bath condition, react at 40-50°C for 2.5-3.5h, add deionized water to obtain reaction solution 1; S2: react the reaction solution 1 obtained in step S1 at 90-100° C. for 1.8-2.2 h, add deionized water and hydrogen peroxide solution in sequence, cool to room temperature, add hydrochloric acid solution, let stand, centrifuge, wash with water and dry to obtain graphene oxide.
3. The method for preparing block copolymer grafted graphene oxide according to claim 1, characterized in that, In step (1), the volume mass ratio of the solvent, graphene oxide, RAFT agent, 4-dimethylaminopyridine and tricyclohexylcarbodiimide is 90-110 mL: 0.5-0.7 g: 2.5-3 g: 0.5-0.6 g: 1.5-1.6 g.
4. The method for preparing block copolymer grafted graphene oxide according to claim 1, characterized in that, In step (1), the RAFT agent is 2-(dodecylthiocarbonylthio)-2-methylpropionic acid or 4-cyano-4-(phenylthioformylthio)pentanoic acid.
5. The method for preparing block copolymer grafted graphene oxide according to claim 1, characterized in that, In step (2), the volume mass ratio of the solvent, the RAFT agent modified graphene oxide, the polyether copolymer and the initiator is 90-110 mL: 0.4-0.6 g: 1.2-1.3 g: 0.1-0.3 g.
6. The method for preparing block copolymer grafted graphene oxide according to claim 1, characterized in that: In step (2), the polyether copolymer is polyethylene glycol methyl ether acrylate, methoxy polyethylene glycol acrylate or allyl polyethylene glycol.
7. The method for preparing block copolymer grafted graphene oxide according to claim 1, characterized in that: In step (3), the volume mass ratio of the solvent, copolymer grafted graphene oxide, polypropanesulfonic acid and initiator is 140-160 mL: 0.4-0.6 g: 12-13 g: 0.1-0.3 g.
8. Block copolymer grafted graphene oxide obtained by the method for preparing block copolymer grafted graphene oxide according to any one of claims 1 to 7.
9. Use of the block copolymer grafted with graphene oxide according to claim 8 in the preparation of cement-based composite materials.
10. The use of the block copolymer grafted with graphene oxide in the preparation of cement-based composite materials according to claim 9, characterized in that: The block copolymer grafted graphene oxide is dispersed in water to obtain a dispersion liquid, and cement, sand and the dispersion liquid are mixed to prepare cement mortar, that is, a cement-based composite material.
Citation Information
Patent Citations
Preparation method of graphene-controlled grafted thermo-sensitive polymer composite material
CN104479058A
Preparation method for nano-composite hydrogel
CN105131209A
Preparation method for nano-composite multi-response hydrogel
CN105131210A
Polycarboxylic acid-modified graphene oxide compound as well as preparation method and application thereof
CN106279580A
Cited By
Waterproof wear-resistant flexible cement-based joint mixture and preparation method thereof
CN121517160A
Heat-resistant PET (polyethylene terephthalate) base film for MLCC (multilayer ceramic capacitor) release film and preparation method of heat-resistant PET base film
CN121572685A
Graphene modified gypsum-based wave-absorbing material and preparation method thereof
CN121974650A